Segmented Trend Analysis of the Eu Renewable Energy Share with Stability Tests - Arkadiusz WEREMCZUK; Mariusz GRĘBOWIEC (Communications of International Proceedings, 2025)
The research examines European Union renewable energy transition speed because it needs to determine if the rising renewable energy percentage since 2019 stems from actual growth or results from new data collection methods. The existing research shows renewable energy consumption continues to rise but fails to identify the 2019 EU-28 to EU-27 transition as a fundamental structural change which might mix up actual patterns with changes in data definitions. The research analyzes annual data from Eurostat (SHARES) and EurObserv’ER for 2012–2023 through segmented linear trend analysis with a specified 2019 break point to detect both level changes and slope variations. The research implements HAC-robust (Newey–West) standard errors and Theil–Sen robust slopes and jackknife influence checks and simple permutation-based stability tests. The renewable energy share in gross final energy consumption grew from 14.2% to 24.6% throughout the entire study period at a rate of 0.95 percentage points (pp) annually. The renewable energy growth rate before 2019 reached 0.62 pp/year but it increased to 1.07 pp/year after 2019 while the estimated level change at the break point reached 1.27 pp. The observed renewable energy percentage in 2023 surpasses the projected linear trend from before 2019 by 3.50 percentage points. The post-2019 segment when extended mechanically produces a policy-independent statistical projection of 26.7% for 2025. The definition-aware estimates provide researchers with a clear reference point for their future panel studies and scenario development work.
Keywords: renewable energy transition; photovoltaics (PV) dominance